The influence of situational leadership style and workload on job stress through locus of control and work balance in retail businesses - Fitri Rezeki; Erina Rulianti; Hamzah Muhammad Mardi Putra; Fachrurazi Fachrurazi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines workplace factors—Locus of Control, Situational Leadership, Work Balance, and Workload—and their collective impact on Job Stress. The urgency of this research arises from the increasing prevalence of job stress that threatens employee productivity and organizational sustainability. The study aims to analyze the direct and indirect effects of these factors in predicting and mitigating stress. A quantitative causal research design was applied with a saturated sample of 95 employees from various organizations. Data were collected through structured questionnaires as the primary instrument, and analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings indicate that Locus of Control significantly predicts Job Stress, emphasizing the role of personal control in reducing stress. Situational Leadership positively influences Locus of Control, while Work Balance reduces Job Stress. Conversely, Workload negatively affects Work Balance, thereby increasing stress levels. Indirect effects were also observed, such as Situational Leadership reducing Job Stress through Locus of Control and Workload influencing stress via Work Balance. The implications suggest that organizations should adopt adaptive leadership, strengthen employees’ sense of control, and manage workloads effectively. These integrated strategies provide valuable insights for leaders, policymakers, and researchers to foster healthier and more productive work environments.